CORPORATE CHARACTERISTICS ON FIRM VALUES WITH MODERATION OF GOOD CORPORATE GOVERNANCE - Lisiantara, Greg Anggana; Jaeni, Jaeni; Nugroho, Arief Himmawan Dwi; Hardiningsih, Pancawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study aims to analyze the moderating role of good corporate governance with the interaction of earning management, corporate social responsibility and debt policy on firm value in the perspective of agency theory and signaling theory. This study used a purposive sampling method with a total sample of 65 go public companies registered with The Indonesian Institute of Corporate Governance in the form of the corporate governance perception index (CGPI) for the period 2019 - 2021. The hypothesis test used is multiple regression analysis with an interaction moderation model. The results of the study prove that earning management has no effect on firm value, CSR has a positive effect on firm value, debt policy has a negative effect on change values, good corporate governance has not been proven to strengthen the effect of earning management on firm value, good corporate governance has been shown to strengthen the effect of CSR on firm value. company. On the other hand, good corporate governance is proven to weaken debt policy on firm value.